Stranded carbon assets and negative emissions technologies - Caldecott, B; Lomax, G; Workman, M (Smith School of Enterprise and the Environment, 2015)
Negative Emissions Technologies (NETs) have the potential to remove carbon dioxide from the atmosphere and this could reduce the impacts of ocean acidification and anthropogenic climate change. To see whether carbon budgets can be extended by NETs and if so, for how long, we quantify the ‘extra space’ that they could create and then examine the potential implications for carbon-intensive sectors.